「昆蟲學」師培課程培育國小師資生開發「昆蟲桌遊」教具與設計測驗卷 Training Pre-service Teachers to Develop Insect Board Games' Aids and Tests through "Entomology" Teacher Education Courses - 盧秀琴 Chow-Chin Lu; 李怡嫻 Yi-Xuan Li (National Changhua University of Education, 2016)
因應知識經濟的時代，要培育具有競爭力的學生就需要有良好的師資培育；故本研究培育國小師資生具備開發「昆蟲桌遊」教具與設計測驗卷的能力，以35 名國小師資生為研究對象，進行「昆蟲學」師培課程的培育。首先教授昆蟲學科知識、ADDIE 模式發展桌 遊教具、如何配合桌遊教具設計「科學過程技能測驗」及「思考智能測驗」。其次，國小師資生玩「昆蟲大富翁」桌遊後，開發「昆蟲桌遊」教具、設計「科學過程技能測驗」及「思考智能測驗」。最後，使用桌遊教具設計評鑑表（ETGD）、科學過程技能評鑑表 （SPTE）、思考智能評鑑表（TITE）檢核之。結果顯示：1. 國小師資生能利用昆蟲學科知識、ADDIE模式開發「昆蟲桌遊」教具。2. 共7 組國小師資生所開發的「昆蟲桌遊教具」獲得AA 到AAA 級的評鑑，達到良好~ 特優等級，顯示師資生具備開發「昆蟲桌遊教具」的能力。3. 7 組國小師資生所設計的「科學過程技能測驗」經過SPTE 評鑑，達到「普通」至「優等」，顯示師資生具備設計「科學過程技能測驗」的能力。4. 共7 組國小師資生所設計的「思考智能測驗」經過TITE 評鑑，達到「普通」至「優等」，顯示師資生具備設計「思考智能測驗」的能力。 In response to the era of the knowledge-based economy, there is a growing need to cultivate competitive students, which requires good teacher education in turn. This study aims to help pre-service teachers advance their abilities through the development of insect board games' aids (IBGA) and two accompanying tests, by means of "Entomology" teacher education courses. Thirty-five pre-service teachers participated in this study. First, in regards to IBGA, the teacher educators taught insect subject knowledge, using the ADDIE model to develop IBGA and to design "Insect Science Process Test, ISPT" and "Thinking Intelligence Test, TIT". Second, after playing "Insects Playing Board Games", the pre-service teachers were divided into 7 groups to design IBGA, ISPT, and TIT. Finally, the qualities of IBGA, ISPT, and TIT developed by the preservice teachers were evaluated using the Evaluation of Board Games Design (EBGD), Science Process Test Evaluation (SPTE), and Thinking Intelligence Test Evaluation (TITE). The results are as follows. 1. Pre-service teachers were able to use the insect subject knowledge and the ADDIE model to develop IBGA. 2. For the development of IBGA, the performances of the 7 groups of pre-service teachers were rated at AA to AAA levels, achieving a status of good to excellent. 3. The 7 groups of pre-service teachers exhibited performances in the development of ISPT that were rated as fair to excellent. 4. The 7 groups of pre-service teachers had performances in the development of TIT that were also rated as varying from fair to excellent.